Video In Situ Snowfall Sensor (VISSS) data for Hyytiälä on 2024-07-10 - Maximilian Maahn; Dmitri Moisseev; Nils Pfeifer (PANGAEA, 2025)
The VISSS is a camera system recording precipitating snowfall from two perspectives. Here, movies and images of falling precipitation particles are provided for one day at station Hyytiälä. For further details on the VISSS see Maahn et al. (2024).
In: Maahn, M et al. (2025): Video In Situ Snowfall Sensor (VISSS) data for Hyytiälä (December 2023 - July 2024) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.981869